Women's cycling and motorcycling from the point of view of jurisprudence and law - Mohammad Reza Rezvan Talab; Saeed Sabouei Jahromi; Reza Poorsedghi (فقه و حقوق خانواده)
In the past, humans used animals for transportation, however, in narrative sources, women riding the saddle is condemned. Considering that nowadays cycling and motorcycling have become popular among women and no independent research has been written in order to explain the jurisprudential foundations of this issue, it is necessary to examine the meaning of the aforementioned traditions and the possibility of generalizing it to cycling and motorcycling. In this article, which was done with the descriptive-analytical method and using library data, it was concluded from the point of view of jurisprudence that the first sentence of women's riding is abhorrent, but due to the lack of unification of the subject, it cannot be generalized to cycling and motorcycling. From the legal point of view, it was also concluded that there is no special law in the Islamic Republic that prohibits women from riding, and only because of the lack of certification for women riding motorcycles, and in certain cases where their riding bikes and motorcycles are considered to be against public modesty, these acts are crimes. It is considered and it cannot be absolutely considered against the law.